2014
DOI: 10.1002/gps.4232
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver burden characterization in patients with Alzheimer's disease or vascular dementia

Abstract: AD caregivers showed a higher burden level than VaD caregivers, and this appeared to be associated with sex and length of time care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 63 publications
(67 reference statements)
4
55
1
6
Order By: Relevance
“…No association was found between the CBI scores and the gender of familial caregivers, as also indicated by a previous study . However, others findings revealed that female caregivers suffer from higher levels of stress than male caregivers …”
Section: Discussionsupporting
confidence: 50%
“…No association was found between the CBI scores and the gender of familial caregivers, as also indicated by a previous study . However, others findings revealed that female caregivers suffer from higher levels of stress than male caregivers …”
Section: Discussionsupporting
confidence: 50%
“…The total score of the CBI ranges from 0 to 96, with higher scores indicating greater caregiver burden. Scores above 36 indicate a risk of burnout; scores close to or slightly above 24 indicate a need to seek some form of respite care [9]. A literature review indicates that the internal consistency of this instrument is between 0.92 and 0.94 [10].…”
Section: Methodsmentioning
confidence: 99%
“…En cuanto a los cuidadores familiares, se observa un perfil típico con predominancia femenina, edad media de 46,9 años, niveles intermedios de escolaridad, estrato socioeconómico entre 1 y 3, con mayor ocupación al hogar, en su mayoría únicos cuidadores, con una media de 137,1 meses de dedicación al cuidado. Lo anterior es relevante considerando que, el ser mujer, con una alta dedicación al cuidado, la falta de recursos económicos y la baja escolaridad son aspectos que se relacionan con la habilidad para cuidar y la sobrecarga del cuidador (20)(21)(22)(23)(24)(25)(26)(27).…”
Section: Discussionunclassified